Investigating educational interpreters' roles and responsibilities: How do they support deaf children in mainstream schools? - Kuscuoglu, Ahmet (2016)
Mainstream education is intended to offer meaningful inclusion, providing appropriate learning services to all. Thus, the general education curriculum is being made accessible to students with hearing impairments, in order to guarantee them equal education opportunities. Primarily responsible for the implementation of inclusive education are educational interpreters, who provide assistance enabling hearing impaired students to gain full access to the content and social life of a mainstream classroom. Although a few studies have highlighted that educational interpreting is a crucial topic in deaf education, it has not yet been adequately studied. The aim of this research is to give voice to the role of educational interpreting, to understand the issues that each expert experiences, and to explore their perceptions in relation to their role and responsibilities. For this investigation, semi-structured interviews were conducted with five educational interpreters and the data was thematically analysed. Five themes were identified, which revealed an in-depth insight into the participants’ knowledge, experiences and perspectives of the current educational process. The findings of this study provide support for previous literature, as they conclude that educational interpreting is vital for deaf or hard-of-hearing (DHH) students. Moreover, the data shows that whilst the main roles and responsibilities of the interpreters relate to establishing an appropriate interpreting model, initiating hearing impaired students’ conversation, and taking into consideration the students’ individual needs required adaptations; this study also highlights various additional roles and responsibilities of interpreters. It highlights the need for legal guidelines, in order to formalise educational interpreters’ role as swiftly as possible.